Price Formation in Markets with Trading Delays - Pintér, Gábor; Üslü, Semih (Management Science, 2025)
We develop a parsimonious price formation model to study information aggregation and information acquisition in the presence of trading delays. If delays apply uniformly to uninformed and informed traders, the level of delays does not affect information aggregation. Traders’ information acquisition incentives are, however, weaker in a market with longer delays. Therefore, the equilibrium fraction of informed traders is lower if delays are longer, establishing an inverse relationship between trading delays and price informativeness. We also show that risk premia and price dispersion tend to be nonmonotonic functions of the level of delays when information acquisition is endogenous. We document novel empirical evidence from the UK corporate bond market, which largely corroborates the implications of our theory. This paper was accepted by Bruno Biais, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2020.01400 .